Agile Project Management: Managing for Success - Crowder, James A (Springer, 2015)
Dr. Crowder has been involved in the research, design, development, implementa tion, and installation of engineering systems from several thousand dollars up to a few billion dollars. Both Dr. Crowder and Ms. Friess have been involved in raving successes and dismal failures (ok, let’s call them learning opportunities) not only in development efforts but in team building and team dynamics as well. Having been involved in agile development projects and team building exercises, both have seen the major pitfalls associated with trying to build teams and, in particular, create successful agile development teams. A general lack of management commitment to the agile development process and a lack of training provided for people working in devel opment teams are two of the major reasons agile teams so often falter or fail. Here we endeavor to discuss some of the major topics associated with team dynamics, individual empowerment, and helping management get comfortable with a new paradigm that is not going away....